Synthesis, characterization and crystal structure of two nickel-based metal-organic frameworks with electrocatalytic activity. Issue 17 (28th November 2022) - Yuan, Yi; Xi, Ben-Jun; Han, Qing-Wen; Wu, Xue-Qian; Wu, Ya-Pan; Chi, Ruan; Lu, Jack Y.; Li, Dong-Sheng
Abstract: Two three-dimensional (3D) nickel-based metal-organic frameworks (Ni(II)-MOFs), {[Ni(adc)(phen)(H2 O)]}n (1, H2 adc = 9, 10-anthracenedicarboxylic acid, phen = 1, 10-phenanthroline) and {[Ni(adc)(bpy)]}n (2, bpy = 4, 4'-bipyridine), were synthesized via a mixed-ligand strategy under hydrothermal and solvothermal conditions. MOF 1 could be simplified as a binodal tfc topology, while 2 possesses a three-fold interpenetrated framework, which is composed of a 4-connected dia network. The phase purity, molecular vibrations, and thermal stability of 1 and 2 have been characterized by powder X-ray diffraction (PXRD), infrared spectroscopy (IR), and thermogravimetric analysis (TG). Further electrochemical experiments reveal that 1 and 2 exhibit good methanol/ethanol oxidation (MOR/EOR) activities, with the optimal current density reaching up to 21.2 (EOR: 25.3) and 15.8 (EOR: 15.3) mA cm −2, respectively. UF0001